Improving Patient Involvement in Medicines Research and Development: A Practical Roadmap - Geissler, Jan; Ryll, Bettina; di Priolo, Susanna Leto; Uhlenhopp, Mary (Therapeutic innovation & regulatory science, 2017)
The value of patient involvement (PI) in medicines research and development (R&D) is increasingly recognized by all health stakeholders. Despite numerous ongoing PI initiatives, PI so far lacks structure and consistency in approach. Limited formal documentation of PI activities further hampers the sharing of experience and learnings, preventing timely and systematic implementation. This article summarizes the outcomes of several multistakeholder discussions during 2013-2016 in a practical roadmap for PI in medicines R&D. The roadmap highlights specific opportunities for PI along the 4 key stages of the medicines R&D life cycle and is illustrated with concrete examples. This roadmap’s aim is to provide a tool to facilitate PI during medicines research and development and is being shared to encourage implementation and further refinement.